Cre/loxP-Based Reversible Immortalization of Human Hepatocytes - Naoya Kobayashi M.D., Ph.D.; Hirofumi Noguchi; Karen A. Westerman; Takamasa Watanabe; Toshihisa Matsumura; Toshinori Totsugawa; Toshiyoshi Fujiwara; Philippe Leboulch; Noriaki Tanaka (Cell Transplantation, 2001)
An ideal alternative to the primary human hepatocytes for hepatocyte transplantation would be to use a clonal cell line that grows economically in culture and exhibits the characteristics of differentiated, nontransformed hepatocytes following transplantation. The purpose of the present studies was to establish a reversibly immortalized human hepatocyte cell line. Human hepatocytes were immortalized with a retroviral vector SSR#69 expressing simian virus 40 large T antigen (SV40Tag) gene flanked by a pair of loxP recombination targets. One of the resulting clones, NKNT-3, showed morphological characteristics of liver parenchymal cells and expressed the genes of differentiated liver functions. NKNT-3 cells offered unlimited availability. After an adenoviral delivery of Cre recombinase and subsequent differential selection, efficient removal of SV40Tag from NKNT-3 cells was performed. Here we represent that elimination of the retrovirally transferred SV40Tag gene can be excised by adenovirus-mediated site-specific recombination.